2014
DOI: 10.1109/jphot.2014.2374595
|View full text |Cite
|
Sign up to set email alerts
|

Photonic Generation of Microwave Pulse Using a Phase-Modulator-Based Sagnac Interferometer and Wavelength-to-Time Mapping

Abstract: We report a new photonic microwave pulse generator using a phasemodulator-based Sagnac interferometer (PM-SI) and wavelength-to-time mapping in a dispersive element. The key significance of the proposed scheme is that the phase of the generated microwave pulse can be continuously tuned by adjusting the bias voltage applied to the PM. Thanks to the wide bandwidth of the PM, high-speed phase modulation of the microwave pulse can be realized. Moreover, the PM-SI is polarization independent, which means that the P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Moreover, the bandwidth of the PM is 40 GHz, which implies that the phase of the generated microwave pulse could be changed with a high speed when a high speed control electrically signal is employed to the RF port of the PM. We have demonstrated this property [8]. Moreover, if a balanced PD is used to convert the optical signal into the electrical signal, the background-free high frequency microwave pulse could also be generated [15].…”
Section: Methodsmentioning
confidence: 72%
See 3 more Smart Citations
“…Moreover, the bandwidth of the PM is 40 GHz, which implies that the phase of the generated microwave pulse could be changed with a high speed when a high speed control electrically signal is employed to the RF port of the PM. We have demonstrated this property [8]. Moreover, if a balanced PD is used to convert the optical signal into the electrical signal, the background-free high frequency microwave pulse could also be generated [15].…”
Section: Methodsmentioning
confidence: 72%
“…where α=V π TE / V π TM [8]. It is obviously indicated that the FSR of the optical comb filter could be changed.…”
Section: Principlementioning
confidence: 99%
See 2 more Smart Citations